Outcomes of non‐myeloablative allogeneic stem cell transplant in older patients with acute myeloid leukaemia in first remission. Issue 11 (18th November 2021) - Nguyen, Phillip C.; Manos, Kate; Fong, Chun Y.; Schwarer, Anthony P.; Tiong, Ing S.; Wei, Andrew H.; Kliman, David; Curtis, David J.
Abstract: The benefits of non‐myeloablative stem cell transplant in older patients with acute myeloid leukaemia are unclear. We compare the long‐term outcomes of this regimen in those aged 55–65 years in first remission with a chemotherapy only cohort that achieved durable morphologic remission. Five‐year overall survival was similar (32% vs 33%, P = 0.90), as was relapse‐free survival (23% vs 20%, P = 0.37). There was a trend for decreased relapse that was balanced against increased non‐relapse mortality with transplantation.